Reduced Audit Quality Behavior Scale: Exploratory and Confirmatory Analysis Based on a Sample of External Auditors in Uganda - Kasigwa, Gerald (Journal of Economics and Behavioral Studies, 2014)
Reduced Audit quality Behavior (RAQB) has been linked to poor quality audits. Whereas reduce audit quality behavior has been studied for some time in developed countries, there has been little empirical research effort in least developed countries like Uganda geared towards understanding and operationalizing the factor structure of reduced audit quality acts. This research set out to establish and confirm a reliable and valid factor structure of reduced audit quality behavior. Data were collected from 351 certified public accountants (CPA’s) practicing as external auditors in Uganda. Exploratory factor Analysis produced a five factor model; with confirmatory factor analysis demonstrating good fit statistics. The reliability of the scales as measured by Cronbach’s alpha, construct reliability and average variance extracted was higher than the recommended minimum values confirming that reduced audit quality acts can be proxied by two dimensions namely; quick review and examination. Researchers in Uganda are advised to use these proxies while studying reduced audit quality behavior.